(untitled) (Docentes 2.0 Journal, 2024)
The Internet and different technological advances have revolutionized both information communication systems and commercial ones, endangering traditional media. For this reason, it was proposed to determine a digital marketing plan to improve the positioning of the paginate. The site serves as an innovative, differentiating, and even strategic support for companies whose purpose is to disseminate advertising in their digital edition. Mixed information was considered; a scientific method was carried out under the descriptive type with administrative documents of the organization and other investigations. There were people from La Paz, with an average age between 25 and 50 years, who had access to the Internet and strategic personnel from the company to contrast opinions with interviews. Subsequently, it was demonstrated how this plan could increase the income of this medium in its web edition with the SEO strategy, promoted with Facebook Ads to implement the project without requiring a large investment. Likewise, achieve alignments with areas involved in generating content and creating commercial ties with institutions outside the newspaper to achieve a fundamental positioning in the digital field, with the professional, editorial, and net trustworthy solvency of a newspaper that is always a legal and historical document.